Actualization of local wisdom in biology learning to support sustainable development toward the well-being of society in the era 6.0: A systematic literature review - Wahyuningtyas, Riska Septia; Silalahi, Marina; Prasmala, Erfitra Rezqi (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Well being society era 6.0 refers to a vision of society that places individual and community well-being at the core of development, utilizing cutting-edge technology and innovation to create a more balanced, healthy and sustainable life. Local wisdom plays a critical role in guiding environmentally responsible behaviors. Comprehensive studies on the utilization of local wisdom in learning to support sustainable development actions are still limited. Therefore, this research was conducted to address the gap. the purpose of this research is to analyze the scope and effectiveness of the utilization of local wisdom in learning processes, as indicated by the integration of local wisdom into learning materials, teaching strategies, and students’ attitudes and competencies, which support culturally relevant and sustainable education. This research used the PRISMA 2020 systematic literature review method, utilizing Scopus as a database. A total of 2249 articles were collected, but only 14 met the criteria for thematic-qualitative analysis. This study found that First, local wisdom-based research on learning is dominantly conducted using qualitative approaches or methods. Second, this theme is an interesting issue and related research has collaborated on a local, national and international scale. Third, the utilization of local wisdom in sustainable development actions is very important to achieve a balance between social, economic, and environmental progress, which aligns closely with biology education through its emphasis on ecological literacy, biodiversity conservation, and the sustainable interaction between humans and their environment. By integrating traditional knowledge and practices that have proven effective in maintaining sustainability. The application of local wisdom in sustainable development involves not only managing natural resources wisely but also strengthening social values that support togetherness and community welfare in the well being society era 6.0.